Efficient Exploitation of Lepidolite Resources: A Review on Beneficiation Techniques, Extraction Methods, and Synergistic Optimization - Jiangang Ku; Xiao Shi; Qian Wang; Hanyu Lin; Hongliang Shang; Zhengchang Shen (Separations)
Lithium is a critical mineral resource. With the development of high-end manufacturing industry, the demand for high-performance lithium-containing chemical raw materials continues to grow. At present, lithium needs to be acquired from a large amount of lepidolite ore, constrained by the existing lithium resource supply limitation quandary, and the industry urgently needs to develop more efficient beneficiation and extraction methods for lepidolite. Findings have suggested mixed collectors (e.g., DDA/SDBS) achieve a 4.99% Li2O grade and 98% recovery at neutral pH, reducing reagent use by 20–30%. Microwave-assisted roasting boosts Li recovery to 95.9% and cuts energy use by 26.9%. Bioleaching with Acidithiobacillus ferrooxidans (A.F.) and rhamnolipid releases 6.8 mg/L Li with a lower environmental impact. Sulfuric acid baking recovers Li (97.1%), Rb (96.0%), and Cs (95.1%) efficiently. Despite challenges in fine-particle recovery and reagent costs, integrated strategies like nanobubble flotation, green collectors, and AI optimization offer sustainable, high-efficiency extraction. This work provides insights for advancing lepidolite processing, balancing economics and environmental stewardship.